Target costing: an approach to competitive advantage / Norlaila Abdullah - Abdullah, Norlaila (2003)
In the quest to meet competitive challenges in today's business landscape, managers often find various options of positioning company's strategy. Regardless of their choices, differentiated or not, managers need tools and approaches that serve as an avenue to becoming better off thann other companies. The writer envisages the use of target costing as one of the path to becoming competitive. Having determined the opportunities available in the market, overcome possible threats, identify the resources, capabilities and core competencies that the company possesses, craft the appropriate strategies, and then the implementation of the chosen alternative that requires basic tools, concepts and operational techniques that would lead to attaining competitiveness. And the writer believes target costing is one of those many avenues